2020
DOI: 10.1074/jbc.ra120.012979
|View full text |Cite
|
Sign up to set email alerts
|

The prohibitin-binding compound fluorizoline affects multiple components of the translational machinery and inhibits protein synthesis

Abstract: Fluorizoline (FLZ) binds to prohibitin-1 and -2 (PHB1/2), which are pleiotropic scaffold proteins known to affect signaling pathways involved in several intracellular processes. However, it is not yet clear how FLZ exerts its effect. Here, we show that exposure of three different human cancer cell lines to FLZ increases the phosphorylation of key translation factors, particularly of initiation factor 2 (eIF2) and elongation factor 2 (eEF2), modifications that inhibit their activities. FLZ also impaired signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Among these ATP- or GTP-binding proteins, we focused our attention on the following: ER chaperone BiP [ 38 40 ]; endoplasmin [ 41 , 42 ]; heat shock protein HSP 90-beta [ 43 ]; members of T-complex protein 1 (TRiC) [ 44 , 45 ], i.e. TCP1, CCT5 and CCT6; heat shock protein 75 kDa [ 46 ]; EF1-α1 [ 47 ]; EF2 [ 48 ], substrate of eEF2K [ 49 , 50 ]; and TER ATPase [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these ATP- or GTP-binding proteins, we focused our attention on the following: ER chaperone BiP [ 38 40 ]; endoplasmin [ 41 , 42 ]; heat shock protein HSP 90-beta [ 43 ]; members of T-complex protein 1 (TRiC) [ 44 , 45 ], i.e. TCP1, CCT5 and CCT6; heat shock protein 75 kDa [ 46 ]; EF1-α1 [ 47 ]; EF2 [ 48 ], substrate of eEF2K [ 49 , 50 ]; and TER ATPase [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jin X et al, considering the interaction of PHBs with proteins that participate in the regulation of translation, analyzed the effect of different PHB-binding compounds on the translation machinery [ 64 ]. These authors found a reduction in new protein synthesis upon fluorizoline treatment in human cell lines, caused by inhibition of eIF2α and eEF2.…”
Section: Discussionmentioning
confidence: 99%
“…Among these ATP-or GTP-binding proteins, we focused our attention on the following: ER chaperone BiP [38][39][40]; endoplasmin [41,42]; heat shock protein HSP 90-beta [43]; members of T-complex protein 1 (TRiC) [44,45], i.e. TCP1, CCT5 and CCT6; heat shock protein 75 kDa [46]; EF1-α1 [47]; EF2 [48], substrate of eEF2K [49,50]; and TER ATPase [51].…”
Section: Identi Cation Of Putative Molecular Targets Of Cpzmentioning
confidence: 99%